International relations and the development of Korea's film industry - Parc, Jimmyn; Ranger, Stephen (Routledge, 2026)
"This book examines the evolution of the Korean film industry, presenting a comprehensive account from the early days of experimental screening to its current period of attracting increased foreign investment. Exploring the Korean film industry's troubled past, this book covers occupation, civil war, authoritarianism, globalisation, and the continued uncertainties amidst geopolitical competition. It differs from other existing works by connecting the development of the Korean film industry to the country's international relations. Furthermore, it considers what impact this had on the industry itself rather than just on the content of the films produced. With such an approach, this book reveals the background and reasons for its achievements, ultimately providing an inspiring example of global success and an applicable benchmark for other film industries seeking their own international breakout. By offering fresh insights and new information linking the past and present of the Korean film industry, the book serves as a useful companion to scholars of cultural studies, business history, Korean studies, and globalization, even if they may not be familiar with the specifics of this dynamic industry. Moreover, this book can serve as a valuable reference for shaping the roadmap of audiovisual sectors-including the film industry-toward a promising future"-- Provided by publisher.
Keywords: Motion picture industry -- Korea -- History.; Motion pictures -- Korea -- History.; elektronické knihy; electronic books